Industrial training report: Ital Auto Sdn. Bhd. (Ferrari Malaysia) / Zahidah Aisyah Mohamed Rasedi - Mohamed Rasedi, Zahidah Aisyah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report summarizes my internship experience at Ital Auto Sdn Bhd (Ferrari Malaysia), which took place from the 22nd of July to the 13th of September. The primary objective of the internship was to gain hands-on experience in the luxury automotive industry, specifically in the operations of Ferrari's exclusive dealership in Malaysia, while contributing to key business functions. During the internship, I was involved in several departments, including Sales, Marketing, and After-Sales Service. My responsibilities included coordinating vehicle servicing schedules, assisting in customer relations by ensuring high-quality service experiences and participating in marketing initiatives to promote Ferrari’s latest models and services. I also contributed to a special project focused on improving customer engagement and loyalty by analyzing customer feedback and suggesting enhancements to the service experience. The key outcomes of the internship include a deep understanding of the Ferrari brand's operational standards, strengthened communication and problem-solving skills, and practical exposure to the dynamics of the luxury car market. This experience has significantly expanded my expertise in customer relations, marketing strategy, and dealership operations, preparing me for future opportunities in the automotive industry.